Medio siglo de Universidad - Lozano Teruel, José Antonio (EDITUM. Ediciones de la Universidad de Murcia, 2025)
Inaugural lesson of the 2008/2009 academic year at the University of Murcia, in charge of the professor José Antonio Lozano Teruel.